2012
DOI: 10.1177/0194599812446678
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Systemic, Topical, and Intralesional Steroid Treatments on Apoptosis Level of Nasal Polyps

Abstract: The apoptotic index in nasal polyps treated with systemic, topical, and intrapolyp injection forms of glucocorticoids was higher than that in the control group. Systemic steroid treatment induced the most apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Interestingly, a clinical study found remarkable differences in the outcomes of topical steroid-treated patients versus those receiving systemic treatment. It has also been reported that systemic GCs are beneficial to OE regeneration or olfactory nerve recovery ( Carbone et al, 2003 ; Heilmann et al, 2004 ; Kapucu et al, 2012 ). The route of administration seems to be very important for reproducing DEX effects, which appears to be hazardous to neuronal recovery independently of the OE lesion model.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, a clinical study found remarkable differences in the outcomes of topical steroid-treated patients versus those receiving systemic treatment. It has also been reported that systemic GCs are beneficial to OE regeneration or olfactory nerve recovery ( Carbone et al, 2003 ; Heilmann et al, 2004 ; Kapucu et al, 2012 ). The route of administration seems to be very important for reproducing DEX effects, which appears to be hazardous to neuronal recovery independently of the OE lesion model.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hands, several studies have indicated that induction of apoptosis in in ammatory cells of the NP, particularly eosinophils, can play a signi cant role in improving the disease conditions [21,28].…”
Section: Discussionmentioning
confidence: 99%
“…Five studies were included in this review -two randomized clinical trials (RCTs) and three retrospective studies (Table 1). [20][21][22][23][24] Inclusion criteria, characteristics and comorbidities for patients in the studies are summarized in Table 2, whereas effects found in the studies are summarized in Table 3. In each of the five studies triamcinolone acetonide (TAA, Kenalog 40 V R ) was injected.…”
Section: Resultsmentioning
confidence: 99%